Avaliação histológica de estratégias de engenharia tecidual para a terapia endodôntica - Duarte, Paulo Carvalho Tobias [UNESP] (2013)
This study aimed to evaluate the tissue response to the implantation of polyethylene tubes filled with a triantibiotic paste (TAP) composed of ciprofloxacin, metronidazole and minocycline conveyed with propylene glycol and polyethylene glycol (macrogol) in subcutaneous tissue of rats and characterize histologically the newly formed tissues post regenerative endodontic procedure employing the blood clot (BC) or BC supplemented with platelet-rich plasma (PRP), bone marrow aspirate (BMA) or a mixture of PRP/ BMA, post-disinfection with TAP. Study to evaluate TAP biocompatibility: Thirty rats received two individual implants of polyethylene tubes filled with TAP or calcium hydroxide paste (CHP) and another empty tube as a control. Thirty other rats received additional polyethylene tubes implants containing the paste vehicles (propylene glycol and macrogol) and an incision procedure (Sham group). After 7, 15, 30, 60, and 90 days, 12 animals were killed, and the tubes were removed and processed for histological examination. The scores ranged from 0 to 3 depending on content of inflammatory cells, the fibrous capsule was considered thin or thick, and necrosis and calcification were recorded as present or absent. The results were analyzed using the Kruskal-Wallis test. Both materials induced moderate reactions at 7 and 15 days which was similar to the control group (p> 0.05) and reduced to mild after 30 days (p> 0.05). The vehicles did not affect the tissue response to the paste. The TAP and their respective vehicles were biocompatible in all experimental periods. Study to histologically evaluate newly formed tissues after regenerative treatment: 20 teeth (40 roots), from 2 Beagle dogs, had their root canals exposed to the oral environment for 90 days to induce apical periodontitis. The canals were prepared until the apical barrier with Protaper...